Needed MIS Competencies to the Job Market: Students’ Perspective (British Journal of Multidisciplinary and Advanced Studies, 2023)
The purpose of this paper is to investigate and identify the sets of competencies that are commensurate with employability requirements. The study follows a quantitative, deductive, and positivist approach. A sample of 62 Lebanese students majoring in management information technology and management information systems (MIT/MIS) was selected conveniently based on the participants' willingness to participate. Students belonged to three Lebanese universities. The research capitalizes on a survey questionnaire divided into three sections. The first section includes knowledge questions, the second section constitutes five parts that address different sets of competencies, and the third section constitutes demographics. Questions and statements followed different styles. Collected data were analyzed using the IBM SPSS version 26.0 package. Data analysis used descriptive, factor, and linear regression analyses. The validity and reliability of the questionnaire were very favorable. Results identified seven factors, each factor constituting 3 to 10 elements. These were condensed using a variable transformation technique and obtained weighted sums modeled using regression analysis. As a result, a competency model was assessed based on the students' current competencies against the necessary employability competencies. The research outcomes serve as a boost to the MIT/MIS competencies theoretical foundations in the context of Lebanon. Moreover, results, though not generalized, serve as an eye-opener for future research. Several recommendations posit the implications to policymakers in higher education and employers in the ICT sectors and other technology-based companies.